Indigenous Knowledge and Utilisation of Strychnos spinosa Lam. in Sub-Saharan Africa: A Systematic Review of Its Medicinal, Nutritional, and Cultural Significance - Sanele Nomfundo Sandisiwe Thothela; Elizabeth Kola; Mwazvita T. B. Dalu; Peter Tshepiso Ndhlovu (Diversity)
In sub-Saharan Africa, indigenous knowledge is a vital source of information about the local environment, including the identification and use of various plant species. One plant species that has attracted much attention in the area is Strychnos spinosa Lam., as local communities utilise it for various purposes, such as medicinal, nutritional, and cultural. A systematic search for eligible studies was carried out by exploring different electronic databases, such as JSTOR, ScienceDirect, PubMed, and Google Scholar. The survey yielded 61 eligible studies, highlighting the diverse of uses of S. spinosa. The literature indicates that 37% of African countries have studied S. spinosa, mainly in Southern Africa. Most studies used semi-structured interviews, but over 70% did not analyse the plant’s nutritional and bioactive compounds. The research highlighted six distinct S. spinosa plant parts used for managing different ailments and conditions in Africa. Roots (25%), along with bark and fruits (23%), are primarily used for digestive disorders and fever; this was followed by leaves (20%) and wood (6%). The least utilised plant part was the radix or cortex (3%). These findings emphasise a significant gap in the understanding of S. spinosa’s nutritional and bioactive compounds, emphasising the need for quantitative research on its phytochemical properties and therapeutic applications within African traditional medicine.